Cross-border cooperation as a component of sustainable regional development of Mongolia - N. Otgonbayar; T. Svirin; Yu. N. Shedko (Вестник университета)
The paper examines the problem of sustainable socio-economic regional development of Mongolia. Based on the analysis of the main indicators of the economy of Mongolia and its aimaks, it has been concluded, that cross-border cooperation plays a significant role in the sustainable development of the economy of Mongolia; due to heterogeneity and signifi diff entiation in terms of development, when developing a strategy for cross-border cooperation, there is a need to take into account the specifics of each individual region and aimak; the solution of the problem of sustainable socio-economic regional development of Mongolia should be implemented on the basis of an integrated approach.